FASHION AND COMMODIFICATION: AN ANALYSIS ON THE GLOBAL PHENOMENON OF SUPREME - Winda Eka Pahla Ayuningtyas; Galant Nanta Adhitya (Universitas Gadjah Mada, 2021)
Globalization is the global information spread and people interconnectivity. It is driven by technological developments in transportation and communication, removing cultural boundaries among nations. Cultural differences are increasingly less tangible and visible in all cultural products, including in fashion. Due to globalization, fashion brands that originate in a certain country can open stores across multiple continents. The invention of the Internet further widens their accessibility by consumers in any part of the world. However, globalization also brings an affordability gap between the upper and the lower classes. Nonetheless, fashion brands can also take advantage of this economic difference in appealing to their consumers. One of those brands is Supreme. Founded in 1994, it became the most sought-after hypebeast brand among street-fashion enthusiasts worldwide. How do they do it in less than 30 years is interesting to analyze. To answer this objective, this article is conducted from the cultural studies standpoint and the case study method. There are three formulas of positioning it adopts in order to grow globally: (1) the commodification African-American community, (2) the use of celebrity endorsement, and (3) the hype of limited-edition releases. Supreme sells oversized streetwear, heavily influenced by Hip-hop culture, a music genre rooted in the lives of African Americans. The brand makes use of celebrities, especially rappers, to endorse its clothes and accessories. It also continually makes headlines by releasing limited-edition products as well as collaborating with well-known figures and brands.